2021
DOI: 10.1186/s13063-021-05534-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical acupoint stimulation for postoperative cognitive dysfunction in geriatric patients with gastrointestinal tumor: a randomized controlled trial

Abstract: Background This study aimed to evaluate the effect of perioperative transcutaneous electrical acupoint stimulation (TEAS) on postoperative cognitive dysfunction (POCD) in older patients who were diagnosed with gastrointestinal tumor and received radical resection of gastrointestinal tumors under general anesthesia. Methods A total of 68 patients who received radical resection of gastrointestinal tumors under general anesthesia were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Whether different electrical stimulation durations have different effects on improving POCD is still uncertain. Some studies showed that continuous stimulation from 30 min before surgery to the end of surgery can improve postoperative POCD in elderly patients and play a protective role in neurological function ( Liu et al, 2021 ; Xi et al, 2021 ; Wei et al, 2022 ). Generally, TEAS intervention is used in the perioperative period, starting more than 30 min before the operation, to reduce the patient’s pain response when the surgeon cuts the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Whether different electrical stimulation durations have different effects on improving POCD is still uncertain. Some studies showed that continuous stimulation from 30 min before surgery to the end of surgery can improve postoperative POCD in elderly patients and play a protective role in neurological function ( Liu et al, 2021 ; Xi et al, 2021 ; Wei et al, 2022 ). Generally, TEAS intervention is used in the perioperative period, starting more than 30 min before the operation, to reduce the patient’s pain response when the surgeon cuts the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the acupoints above can activate Qi and blood circulation and regulate viscera functions to balance the qi and blood, dredge meridians and qi activity, strengthen the body resistance to eliminate pathogenic factors, and improve immunity and fatigue resistance. [41][42][43] TEAS needs to be manually operated step by step. It was difficult for the discharged patients to operate this method.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these 2 acupoints, together with Zhongwan, can reinforce qi, nourish blood, and invigorate the spleen and stomach; Taixi is the source acupoint of the kidney meridian which can nourish the kidney and yin and supply vital essence and marrow. The combination of the acupoints above can activate Qi and blood circulation and regulate viscera functions to balance the qi and blood, dredge meridians and qi activity, strengthen the body resistance to eliminate pathogenic factors, and improve immunity and fatigue resistance 41–43…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the incidence of POCD in geriatric patients with gastrointestinal tumors is 40%. 37 The pilot study showed that esketamine administration could reduce the incidence of PND by 30%. Given a power of 85% and a significance level of 5%, the sample size was determined to be 66, with 33 subjects in each arm using a 1:1 ratio for the groups.…”
Section: Methodsmentioning
confidence: 99%